2014
DOI: 10.1038/srep03663
|View full text |Cite
|
Sign up to set email alerts
|

Cultured 3T3L1 adipocytes dispose of excess medium glucose as lactate under abundant oxygen availability

Abstract: White adipose tissue (WAT) produces lactate in significant amount from circulating glucose, especially in obesity;Under normoxia, 3T3L1 cells secrete large quantities of lactate to the medium, again at the expense of glucose and proportionally to its levels. Most of the glucose was converted to lactate with only part of it being used to synthesize fat. Cultured adipocytes were largely anaerobic, but this was not a Warburg-like process. It is speculated that the massive production of lactate, is a process of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 51 publications
13
63
0
Order By: Relevance
“…0.2 mM of dissolved O2). These values were in the range of those measured under the same conditions 28 . The calculated pCO2 was in the range of 5 kPa, corresponding to 1.7 mM of dissolved CO2 41 .…”
Section: Conditions For the Incubation Of Adipocytessupporting
confidence: 67%
See 4 more Smart Citations
“…0.2 mM of dissolved O2). These values were in the range of those measured under the same conditions 28 . The calculated pCO2 was in the range of 5 kPa, corresponding to 1.7 mM of dissolved CO2 41 .…”
Section: Conditions For the Incubation Of Adipocytessupporting
confidence: 67%
“…We have found, recently, that adipocytes glycolyze huge amounts of glucose to lactate and glycerol 28 , acting, essentially, as an anaerobic tissue under normoxic conditions, such as those used in the present study, and this mechanism extends to the in vivo conditions 29 . We have also found that WAT contains a full urea cycle 58 and a potentially active amino acid metabolism 14 .…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations